2008
DOI: 10.1097/brs.0b013e3181808c4e
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Widespread Pain in Patients With Occupational Spinal Disorders

Abstract: A surprisingly high frequency of CDOSD patients participating in interdisciplinary rehabilitation met criteria for CWP, though the diagnosis was generally unknown to the patient. In this large workers' compensation cohort, CWP was not associated with longer periods of disability, more prerehabilitation surgery or higher pain self-report. With appropriate rehabilitation, CWP patients can have equally successful work return and health utilization outcomes compared to non-CWP patients, despite having significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 57 publications
1
10
0
Order By: Relevance
“…However, recent research indicates that the presence of pain is associated with depressed mood in a range of other illnesses, where pain is one symptom but not necessarily the cardinal symptom for which the patient is seeking treatment. For example, in patients following spinal cord injury, the experience of chronic widespread pain is associated with psychiatric symptoms [21]. Similar findings have been reported in patients with multiple sclerosis [22], cancer [23] and arthritis [24].…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…However, recent research indicates that the presence of pain is associated with depressed mood in a range of other illnesses, where pain is one symptom but not necessarily the cardinal symptom for which the patient is seeking treatment. For example, in patients following spinal cord injury, the experience of chronic widespread pain is associated with psychiatric symptoms [21]. Similar findings have been reported in patients with multiple sclerosis [22], cancer [23] and arthritis [24].…”
Section: Introductionsupporting
confidence: 57%
“…Participants in these studies typically have a high mean number of illnesses (e.g. TG Mayer, BL Towns, R Neblett, BR Theodore and RJ Gatchel [21] had a mean of three illnesses) and therefore, there is good reason to believe that these approaches would result in significant patient gain for those with complex needs, such as multi-morbidity. This is especially true of the older (> 75 years) and more frail elderly, where pain has been shown to be a particularly important challenge [57].…”
Section: Discussionmentioning
confidence: 99%
“…In patients with chronic LBP it has been reported that 25–38% develop chronic widespread pain [164166], and the condition is closely associated with systemic co-morbidity and psychological disorders [167]. …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, patients with CWP/FMS often report partial or whole work incapacity, increased sick-leave, and poor quality of life and health. [68] Clearly, CWP is a major health burden.…”
Section: Introductionmentioning
confidence: 99%